2018
DOI: 10.4103/jisp.jisp_30_18
|View full text |Cite
|
Sign up to set email alerts
|

Awareness among intensive care nurses regarding oral care in critically ill patients

Abstract: Background:Oral health and general health are interdependent which influence each other through biological, psychological, emotional, and developmental factors. As patients in Intensive Care Unit (ICU) are completely dependent on the caregivers, the knowledge, attitude, and practices of the nurses influence the recovery of patients to a greater extent.Objectives:Unfortunately, oral health problems are usually overshadowed by other serious needs in critically ill patients. In addition, nursing staff appear to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 28 publications
1
16
0
9
Order By: Relevance
“…Our results con rm this, to some extent. Although many studies have shown no statistically signi cant difference between years of nursing service and prevention of VAP [21][22][23] , these studies all underscore the point that nursing training directly affects the incidence of VAP. In addition, a study highlighted the importance of new undergraduate courses and training, as well as postgraduate training, in improving nurse compliance [24] .…”
Section: Discussionmentioning
confidence: 96%
“…Our results con rm this, to some extent. Although many studies have shown no statistically signi cant difference between years of nursing service and prevention of VAP [21][22][23] , these studies all underscore the point that nursing training directly affects the incidence of VAP. In addition, a study highlighted the importance of new undergraduate courses and training, as well as postgraduate training, in improving nurse compliance [24] .…”
Section: Discussionmentioning
confidence: 96%
“…A presença de um cirurgião-dentista na equipe multiprofissional nas UTIs é de extrema valia e importância 25,28,[39][40][41][42] . Galhardo et.…”
Section: Foramunclassified
“…O artigo de Sreenivasan et. al 42 Além da padronização dos protocolos de cuidados orais, o treinamento e a conscientização da equipe fazem parte da estratégia de prevenção da PAVM. Assim, é a partir desse princípio que conseguiremos atingir um padrão superior de assistência e promover a segurança do paciente.…”
Section: Foramunclassified
“…Nursing care, especially in Intensive Care Units (ICUs), needs constant awareness and vigilance because the nurses provide critical care and living support for acutely unwell and vigilance because the nurses provide critical care and living support for acutely unwell and injured patients (2,3). The patients in ICUs are completely depending on care givers so that, the nurses' knowledge, attitude, and practices have an impact on the patients' recovery to a greater extent (4). Care is the reason for the existence of the nursing profession and is a global concept of nursing and the nursing process used to ensure this care (5) .…”
Section: Introductionmentioning
confidence: 99%